Why does Perth stand alone? Interviews with subject matter experts about the drivers of settlement in Western Australia - Wilkinson III, George S.; Haslam McKenzie, Fiona; Bolleter, Julian (Australian geographer, 2022)
Australian non-capital cities are overshadowed by their state capitals. High state-level urban primacy is especially true of Western Australia. Various theories in economic geography might explain the west Australian settlement pattern. Few are grounded in the experience of those with power over and/or knowledge of development. To study this experience and compare it with theory we conducted 37 in-depth interviews with decision-makers and subject matter experts to understand their explanations of Western Australia's settlement pattern. In addition to well-known determinants of settlement, such as environmental constraint and first-mover advantages, a majority of participants attributed Perth's dominance to centralised political institutions, poor infrastructure provision to non-capital city regions, few bottom-up growth avenues, and an unmet need to devolve power. Most participants believed centralisation in Perth warrants intervention. The most reoccurring ideas are presented and discussed.